Uzual And Occasional Use Of Phraseological Units Of The Uzbek Language - Boltaev A.A, Boltaeva B, Sherboeva N, Siddigova C (International Journal of Advanced Science and Technology, 2020)
This article deals with the uzal and occasional use of phraseological units.